2015
DOI: 10.1021/cs502036d
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Supported Palladium Nanoparticles during Methane Oxidation

Abstract: Time-resolved in situ energy-dispersive X-ray absorption spectroscopy and mass spectrometry have been used to correlate changes in chemical state of alumina and ceria supported palladium nanoparticles with changes in activity and selectivity for methane oxidation. Specifically, modulation excitation spectroscopy experiments were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 42 publications
10
67
0
Order By: Relevance
“…Using a quantum/classical approach they demonstrated that Pd(IV) oxide would be stabilized on ceria due to its interaction with the support, yielding low methane activation barriers. The enhancement in oxide formation of Pd clusters due to the effect of CeO 2 is in agreement with the work of Farrauto et al 53 and Nilsson et al 54 Although sophisticated sampling and advanced optimization methods may correctly identify the global minimum structure of the cluster catalyst, it is not the ultimate, complete representation of the active site. First of all, unlike extended surfaces, catalytic clusters do not stay put in their starting global minimum during the reaction.…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not supporting
confidence: 89%
“…Using a quantum/classical approach they demonstrated that Pd(IV) oxide would be stabilized on ceria due to its interaction with the support, yielding low methane activation barriers. The enhancement in oxide formation of Pd clusters due to the effect of CeO 2 is in agreement with the work of Farrauto et al 53 and Nilsson et al 54 Although sophisticated sampling and advanced optimization methods may correctly identify the global minimum structure of the cluster catalyst, it is not the ultimate, complete representation of the active site. First of all, unlike extended surfaces, catalytic clusters do not stay put in their starting global minimum during the reaction.…”
Section: The Global Minimum Structure Of the Cluster Catalyst: Not supporting
confidence: 89%
“…Palladium is ak nown efficient catalyst for CH 4 oxidation and has been studied extensively.V arying hypotheses of the active phase have been reported, from aP dO-like phase to Pd 0 . [1] Unfortunately,o fa ll the catalysts currently reported, none are sufficiently active under coldstart conditions,w ith most catalysts requiring light-off temperatures of around 400 8 8C. [2] Such high temperatures are required because of the high activation barriers to CH 4 dehydrogenation;particularly formation of surface adsorbed CH 3 *a nd H*, which is thought to be the rate-determining step.F or example,J ørgensen and Grçnbeck predicted that the extraction of the first Hfrom CH 4 had activation barriers of 0.99 and 0.79 eV over Pd(111) and Pd(100), respectively.…”
mentioning
confidence: 99%
“…[28][29][30][31] In fact, the XANES signals are mostly sensitive to the oxidation state of an element, and less sensitive to its local coordination and structure. 32 Hence, from the spectroscopic point of view, PdO and Pd(OH) 4 2− cannot be easily discriminated, whereas the redox change from Pd to Pd(II) can be easily monitored, even using a single fixed energy of 24370 eV (Fig.…”
Section: Discussionmentioning
confidence: 99%